Analysis of 3GPP LTE MAC Layer Procedure - Biswas, Sushovan; Raj Gupta, Rishi; Kr Das, Malay (International Journal of Computer Sciences and Engineering, 2025)
With the advent of telecommunications from the era of GSM to nowadays extensive LTE services multiple process have been metamorphosed to improve the efficiency of the services. Introduction of one such technique from 3GPP TS release version 10.0.0 to release 10.0.1 is Buffer Status Report and cancellation. To clarify the ambiguity about the quantity of data to be transferred and correspondingly allocation of bearer’s network typically requires the buffer status reports from User Equipment’s (UE) for scheduling of uplink resources. Extensive studies and research have established that the efficiency of scheduler will increase with the accuracy of the buffer status reports. Generally, in this paper, we propose and method for a UE to report accurate buffer status reports and also considering the circumstances to cancel the BSR in 3GPP Long Term Evolution.